The effect of teaching religious principles on the infants' growth and development - Tahereh Mokhtaryan Gilani; Fatemeh Ghodrati; Zahra Yazdanpanahi; Sedigheh Amooee; Marzieh Akbarzadeh (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Teaching religious principles can inevitably strengthen the mothers' motivation and may improve the infant's growth indices. This study aimed to investigate the effect of teaching religious principles on the infants' growth and development from birth up to the age of 3 months. METHODS: In a randomized controlled tria1, 84 primiparous women who had average or weak religious attitude were randomly divided into intervention and control groups in 2013. The intervention group attended six 90-min sessions of religious education held once a week. The control group received the routine pregnancy care. Data were collected through physical growth indices and Denver's questionnaire. RESULTS: A significant difference was found between the intervention and control groups regarding the head circumference at birth (34.61 ± 1.51 vs. 32.97 ± 6.98). Besides, a significant relationship was observed between religious knowledge before delivery and infants' development in gross motor skills (P = 0.047, r = 0.114) and major motor skills (P = 0.019, r = 0.359) at 1 month of age, and also language skills (P = 0.015, r = 0.119), major motor skills (P = 0.008, r = 0.404), and fine motor skills (P = 0.035, r = 0.425) at the age of 3 months in the intervention group. CONCLUSION: Training the pregnant mothers regarding religious principles was effective in some indices of infants' physical growth and development.